Inovasi Media Edukatif dalam Pembelajaran Trigonometri dan Statistika di Sekolah Kejuruan Perbatasan - Seo, Hendro Usa Juniano; Guteres, Ilda; Jagom, Yohanes Ovaritus; Gawa, Maria Gracia Manoe; Lakapu, Meryani (Actual Insight, 2025)
This community service program aimed to enhance students’ understanding and interest in mathematics, particularly in topics often perceived as difficult—trigonometry and statistics. The activity was conducted at SMKS St. Willibrodus Betun, Malaka Regency, involving six students from Universitas Katolik Widya Mandira (UNWIRA) and Universidade Oriental Timor Lorosa’e (UNITAL) Timor Leste. The implementation method consisted of educational outreach using contextual and participatory approaches, along with inclusive language (Indonesian, Tetum, and English) tailored to the students’ and facilitators’ backgrounds. Trigonometry was taught using a student-designed teaching aid called the